2019
DOI: 10.1080/07036337.2019.1665659
|View full text |Cite
|
Sign up to set email alerts
|

The new European border and coast guard agency: pooling sovereignty or giving it up?

Abstract: In 2016, the European Parliament and the Council adopted a legislative act creating and regulating a new European Border and Coast Guard Agency. Its Article 19 states thatshould a Member State's failure to control its own borders jeopardize the collective effort to monitor the external borders of the Schengen Areathe new Agency could take over the management of border control operations in that Member-State. This transfer of power begs a crucial question regarding EU's conflict of sovereignties. First, this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Recent studies of the EU have tended to analyse the European border regime as a whole. Such analyses have often concluded that the European border regime is weak, intergovernmental, legalistic or merely co-ordinating (Börzel and Risse, 2018;den Heijer et al, 2016;Schimmelfennig, 2018). For instance, Genschel and Jachtenfuchs (2018) argue that 'the Schengen agencies (…) are fairly small, weak and intergovernmental in structure ' (p. 183).…”
Section: The Decoupling Of Immigration Policy and Border Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of the EU have tended to analyse the European border regime as a whole. Such analyses have often concluded that the European border regime is weak, intergovernmental, legalistic or merely co-ordinating (Börzel and Risse, 2018;den Heijer et al, 2016;Schimmelfennig, 2018). For instance, Genschel and Jachtenfuchs (2018) argue that 'the Schengen agencies (…) are fairly small, weak and intergovernmental in structure ' (p. 183).…”
Section: The Decoupling Of Immigration Policy and Border Controlmentioning
confidence: 99%
“…1(2)). It was small, wielded a relatively limited budget and held no supranational powers (Deleixhe and Duez, 2019; Wolff and Schout, 2013).…”
Section: The Asymmetry Of the Eu's Border Regimementioning
confidence: 99%
“…It is this action that makes us think about the relationship between the concepts of territory, border and sovereignty. This process of externalizing borders is described in the context of a broader study of territoriality, which suggests how the fluctuating geography of borders redefines our understanding of territoriality and changes longstanding practices of sovereignty [37,38]. This is being done by many actors on the ground and represented by the United States and Canada, as well as other countries in the region, such as the European Union.…”
Section: Economic Consequences Of Bordering Between Neighbouring Statesmentioning
confidence: 99%
“…In this vein, Frontex and its risk analysis become a tool serving to justify European Commission's decision-making. Nevertheless, this seems quite problematic in the case of Frontex, as, though technocratic, it constitutes an agency that has enhanced competences in the sensitive area of border management, which relates to national state power and sovereignty (Deleixhe & Duez, 2019). It should be mentioned, that within this stream, Horii's work refers to a professional community by drawing attention to intra-organisational behaviour and institutional homogenisation.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, since the 2016 Regulation, EIBM has become a shared responsibility between Frontex and member states. In this context, EU member states are obliged to contribute to the agency with staff and technical equipment (Carrera & den Hertog, 2016: 2), whereas the agency has the 'right to intervene' operationally on the ground of a member state irrespective of its consent (Regulation, 2016) impacting on traditional undertandings of sovereignty (Deleixhe & Duez, 2019).…”
Section: Frontex As a Border Control Actormentioning
confidence: 99%